An Integrative Review of the Psychosocial Impacts of COVID-19 on Frail Older Adults: Lessons to Be Learned in Pandemics - Arya Hamedanchi; Hamid Reza Khankeh; Yadollah Abolfathi Momtaz; Nasibeh Zanjari; Mohammad Saatchi; Tahereh Ramezani; Ahmad Delbari (Health in Emergencies & Disasters Quarterly, 2023)
Background: The COVID-19 pandemic has inflicted tremendous pressure on people, including older adults. Frail older adults are more susceptible to the adverse consequences of the pandemic. Although many studies have investigated the susceptibility and poor medical outcomes of COVID-19 in frail people, a few studies have explored the psychosocial effects of the pandemic on this group of vulnerable people. This study overviews the psychosocial consequences of the pandemic and necessary public interventions for frail older adults. Materials and Methods: An integrative review method was utilized to gather, analyze, and structure the study data. PubMed, Web of Science, and Scopus databases were searched to extract the published English papers based on a designed strategy. The keywords and used Boolean operators in their titles or abstracts were ([“COVID-19” OR “CORONA” OR “SARS-CoV-2”] AND [“frail” OR “frailty”]). A total of 50 articles (47 quantitative, 2 qualitative, and 1 mixed method) were selected for the final analysis. Results: Anxiety and depression were reported as the most significant psychological consequences in the related studies. The results also indicated the social relations of older frail people and their access to health services noticeably reduced during the pandemic. On the other hand, physical exercise programs, telemedicine, and reading activities were the most preventive measures to mitigate the impacts of public restrictions during the pandemic. Conclusion: The results of this review can assist policymakers in reflecting appropriate psychosocial support for frail seniors during the pandemic. As most studies on the psychosocial aspects of the COVID-19 pandemic among frail older adults are quantitative and have been performed in developed countries, it is suggested to conduct further qualitative studies. These studies should explore frail older adults’ experiences and perceptions and their challenges during the pandemic, particularly in developing countries.